Safety and efficacy of a tincture derived from Artemisia vulgaris L. (Mugwort tincture) when used as a sensory additive in feed for all animal species. (6th November 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of a tincture from Artemisia vulgaris L. (Mugwort tincture) when used as a sensory feed additive for all animal species. The product is a water/ethanol ■■■■■ solution, with a dry matter content of approximately 1.7%. The product is specified to contain a minimum of 0.01% hydroxycinnamic acid derivatives (expressed as chlorogenic acid). However, since the 74% of the dry matter fraction of the additive remains uncharacterised, the FEEDAP Panel cannot conclude on the safety of the additive at the proposed use levels of up to 400 mg/kg complete feed for all animal species or for the consumer. No specific data were provided by the applicant regarding the safety of the additive for users. In the absence of data, no conclusions can be drawn on the additive's potential to be a dermal/eye irritant or a skin sensitiser. A. vulgaris is native to Europe. Consequently, the use of a tincture derived from the plant at the maximum proposed dose is not considered to be a risk for the environment. Since the major components of the additive are recognised to provide flavour in food and its function in feed would be essentially the same, no demonstration of efficacy is considered necessary.